The scarcity dilemma in lupus nephritis: A rare case of diffuse alveolar hemorrhage and its multitargeted management - Badrinath, Thannushree Aritakulu; Pathak, Nabadwip; Thampan, Sebin John; Gunasekaran, Indira (Ukrainian Journal of Nephrology and Dialysis, 2024)
Systemic lupus erythematosus (SLE) is an autoimmune disease that often involves lupus nephritis, affecting the kidneys. A severe and rare complication of SLE is diffuse alveolar hemorrhage. When both conditions occur together in a young male, the prognosis is generally poor. Managing SLE effectively requires strong immunosuppression, but despite the availability of new immunosuppressive agents, treating lupus nephritis remains challenging. Many patients do not achieve complete remission with conventional treatments, highlighting the need for better therapeutic strategies. Research indicates that targeting multiple components of the immune system can be more effective for patients who do not respond to standard treatments, leading to the adoption of multitarget therapy in lupus nephritis. We present a case report of a young male with biopsy-proven Class IV lupus nephritis and diffuse alveolar hemorrhage who did not respond well to conventional treatments but showed improvement with a multitargeted treatment regimen.